Maternal Nutrition During Gestation Alters Histochemical Properties, and mRNA and microRNA Expression in Adipose Tissue of Wagyu Fetuses - Zhang, Yi; Otomaru, Konosuke; Oshima, Kazunaga; Goto, Yuji; Oshima, Ichiro; Muroya, Susumu; Sano, Mitsue; Roh, Sanggun; Gotoh, Takafumi (Frontiers in Endocrinology, 2022)
We hypothesized that maternal low or high nutrition would give unique effects to morphological and molecular dynamics in adipose tissue of fetus of fatty breed Wagyu (Japanese Black) cattle which produce highly marbled beef. This study aimed to determine the effects of maternal energy intake in Wagyu cows, during gestation on fetal adipose tissue development, histochemical properties, and gene and microRNA (miRNA) expression. Cows were allocated to one of two nutritional energy groups: 120% (HIGH) or 60% nutritional requirements of (LOW). Fetuses (n = 6 per treatment) were removed from pregnant cows by cesarean section at fetal age 260 ± 8 days and euthanized. Subcutaneous adipose tissue (SAT), thoracic cavity visceral adipose tissue (TVAT), and perirenal adipose tissue (PAT) were collected for analysis. In histochemical analysis, in SAT and PAT, HIGH fetuses had greater diameter of adipocytes than LOW fetuses (P<0.05). Only in SAT, LOW fetuses had more Leptin (LEP) mRNA and tended to have more Peroxisome Proliferator-Activated Receptor gamma (PPARG) CCAAT-enhancer-binding proteins alpha (CEBPA) and Glucose transporter (GLUT) 4 mRNA(P<0.10). In all SAT, TVAT, and PAT, LOW fetuses had higher levels of the brown adipose tissue (BAT) biomarkers Uncoupling Protein (UCP) 1 and PPARG coactivator (PGC) 1α mRNA than HIGH fetuses (P<0.08). Meanwhile, in the other adipose tissue, LOW fetuses had lower PPARG, CEBPA, and Zinc Finger Protein (ZFP) 423 (in TVAT and PAT), FASN (in TVAT), LEP and GLUT4 mRNA (in PAT; P<0.10). In particular, in TVAT and PAT, LOW fetuses exhibited lower expression of WAT biomarkers (PPARG and ZFP423). Differential expression of various miRNAs related to adipogenesis between the LOW and HIGH fetuses was detected in an adipose tissue-specific manner (P<0.10). Based on adipose tissue-specific effects of maternal nutrition, these findings suggested that poor maternal nutrition in Wagyu cattle increased BAT development in SAT, TVAT and PAT, while elevated maternal nutrition stimulated fetal SAT development compared with that of TVAT and PAT.